Successional trophic complexity and biogeographical structure of eukaryotic communities in waterworks' rapid sand filters. Issue 11 (13th September 2019) - Bugge Harder, Christoffer; Nyrop Albers, Christian; Rosendahl, Søren; Aamand, Jens; Ellegaard-Jensen, Lea; Ekelund, Flemming
ABSTRACT: As groundwater-fed waterworks clean their raw inlet water with sand filters, a variety of pro- and eukaryotic microbial communities develop on these filters. While several studies have targeted the prokaryotic sand filter communities, little is known about the eukaryotic communities, despite the obvious need for knowledge of microorganisms that get in contact with human drinking water. With a new general eukaryotic primer set (18S, V1-V3 region), we performed FLX-454 sequencing of material from 21 waterworks' sand filters varying in age (3–40 years) and geographical location on a 250 km east–west axis in Denmark, and put the data in context of their previously published prokaryotic communities. We find that filters vary highly in trophic complexity depending on age, from simple systems with bacteria and protozoa (3–6 years) to complex, mature systems with nematodes, rotifers and turbellarians as apex predators (40 years). Unlike the bacterial communities, the eukaryotic communities display a clear distance–decay relationship that predominates over environmental variations, indicating that the underlying aquifers feeding the filters harbor distinct eukaryotic communities with limited dispersal in between. Our findings have implications for waterworks' filter management, and offer a window down to the largely unexplored eukaryotic microbiology of groundwater aquifers. Abstract : This paper shows how several unique microbial ecosystems which exist on waterworks' sand filters build up over time, and how they differ markedly from each other over distances of <200 km.